PERTANGGUNGJAWABAN PIDANA NOTARIS TERHADAP AKTA OTENTIK YANG DIBUAT TERINDIKASI PEMALSUAN - Marchelina Rante; Hernita Matana (Paulus Law Journal, 2021)
A notary is an authorized public official whose main obligation is to make authentic deeds based on a professional code of ethics, related to the widespread indications of forgery of the authentic deeds, of course this needs to be accounted for by the notary himself. This study aims to identify and explain the criminal liability of a Notary against an authentic deed made and indicated forgery and to find out the legal status of a deed made by a Notary that caused a dispute. The data collection carried out in this research is by interview and literature study as well as the applicable legislation. Data were analyzed descriptively qualitatively. The results of the study indicate that if the notary is proven to have falsified or falsified the authentic deed he made and caused harm to interested parties, the notary can be sentenced to criminal, civil, and administrative sanctions. The legal status of the deed that is proven to be falsified by the Notary who made it, which can be canceled, null and void, has the power of proof as an underhand deed, canceled by the parties themselves and canceled by a court decision that has permanent legal force. However, the status or position of the Notary deed can’t be carried out jointly, but only applies to one, in accordance with a permanent court decision.